Supporting recovery in patients with psychosis using adult mental health teams (REFOCUS): a multi-site cluster randomised controlled trial - Slade, Mike; Bird, Victoria; Clarke, Eleanor; Le Boutillier, Clair; McCrone, P.; Macpherson, Rob; Pesola, Francesca; Wallace, Genevieve; Williams, Julie; Leamy, Mary (Elsevier, 2015)
Background: Mental health policy in many countries is oriented around recovery. The evidence base for service-level pro-recovery interventions is lacking. Methods: Two-site cluster randomised controlled trial in England (ISRCTN02507940). REFOCUS is a one-year team-level intervention targeting staff behaviour (increasing focus on patient values, preferences, strengths, goal-striving) and staff-patient relationships (coaching, partnership). 27 community-based adult mental health teams were randomly allocated to treatment-as-usual (n=13) or treatment-as-usual plus REFOCUS (n=14). Baseline (n=403) and one-year follow-up (n=297) outcomes were assessed for randomly selected patients with psychosis, representing 88% of target recruitment. Primary outcome was recovery, assessed using Questionnaire about Processes of Recovery (QPR). Findings: Intention-to-treat analysis using multiple imputation found no difference in QPR Total (control 40·0 (s.d.10·2), intervention 40·6 (s.d.10·1), adjusted difference 0·68, 95%CI: -1·7 to 3·1, p=·58), or sub-scales. Secondary outcomes which improved in the intervention group were functioning (adjusted difference 6·96, 95%CI 2·8 to 9·2, p<·001) and staff-rated unmet need (adjusted difference 0·80, 95%CI 0·2 to 1·4, p=·01). This pattern remained after covariate adjustment and completer analysis (n=275). Higher-participating teams had higher staff-rated pro-recovery behaviour change (adjusted difference -0·4, 95%CI -0·7 to -0·2, p=·001) and patients had higher QPR Interpersonal scores (adjusted difference -1·6, 95%CI -2·7 to -0·5, p=·005) at follow-up. Intervention-group patients incurred £1,062 (95%CI -£1,103 to £3,017) lower adjusted costs. Interpretation: Supporting recovery may, from the staff perspective, improve functioning and reduce needs. Overcoming implementation barriers may increase staff pro-recovery behaviours and interpersonal aspects of patient-rated recovery. Funding: National Institute for Health Research.